A qualitative research on perceptions and experience of patients with sudden deafness (突发性聋患者疾病感受和体验的质性研究) - ZHANG Shan (张珊); CHEN Li (陈丽) (中西医结合护理)
Objective To investigate the perceptions and experience of patients with sudden deafness, and provide reference for clinical interventions on sudden deafness. Methods Totally 16 patients with sudden deafness were recruited using a purposive sampling method, A face-to-face semi-structured method was adopted, and qualitative data was analyzed Colaizzis method of phenomenological analysis. Results Four themes were identified: difficulty in accepting the disease, reduced quality of life(changes in daily life, being disturbed by accompanying symptoms), uncertainty in illness(inadequate awareness of the disease, worse-than-expected treatment outcome ) and negative emotions(anxiety and depression, losing confidence in treatment). Conclusion Clinical nursing staff should pay more attention on physical and psychological needs and conflicts among patients with sudden deafness, and establish individualized and targeted nursing measures. (目的 深入了解突发性聋患者的疾病感受和体验, 为突发性聋患者的护理干预策略制订提供参考依据。方法 采用目的抽样选取突发性聋患者共16人进行访谈, 以半结构式深入访谈形式收集资料, 并采用质性研究中的现象学研究方法分析提炼主题。结果 突发性聋患者的疾病感受和体验4个主题: 难以接受疾病状态, 生活质量下降(生活状态改变、受伴随症状困扰), 疾病不确定感(疾病认知缺乏、治疗效果不及预期), 负性情绪(焦虑抑郁、对治疗失去信心)。结论 突发性聋患者在生理和心理方面存在诸多需求与困扰, 临床护理人员需予以重视, 结合患者自身需求, 制定个体化、针对性护理措施。)